40Ar/39Ar Cooling Ages of the Paraguay Belt in the Nova Xavantina Region (MT): Tectonic Implications for Western Gondwana Collage - Geraldes, Mauro César; Santos, Anderson Costa dos; Santos, Werlem Holanda dos; Tassinari, Colombo (Anuário do Instituto de Geociências, 2019)
40Ar/39Ar analysis were carried out on biotite crystals from the Paraguay Belt rocks in Nova Xavantina region (Mato Grosso State, Brazil) with the purpose to constrain the age from the regional metamorphic event. The samples are metavolcanic mafic rocks deformed during Brasiliano-Panafrican events. The 40Ar/30Ar plateau ages range from 541.6 ± 0.4 Ma to 531 ± 0.6 Ma and define the cooling period of regional metamorphic event related to the collision between the Amazonian craton and Paranapanema block, the final stages of the western Gondwana assembly. The Paraguay Belt association cropping out in this region comprise metamorphosed sedimentary (chemical and siliciclastic) and volcanic (basic and intermediary) rocks related to an ocean floor geological setting (Xavantina Ocean). This work presents two new ages for two biotite grains and compares with literature data suggesting that the 40Ar/39Ar data here reported and geological evidence indicates that the metabasic rocks present metamorphic ages in the range from 541 Ma to 531 Ma and their protolith about 700-648 Ma or older.